Correlations of Oxytocin, Fibroblast Growth Factor-21 and Hepatocyte Growth Factor in Diabetic and non-Diabetic Metabolic Syndrome Patients: Acase- Control Study from Jordan - Kasabri, Violet; Al-Musa, Khaled; Bulatova, Nailya; Al-Rawashdeh, Amani; Khawaja, Nahla; Bustanji, Haider; Hyasat, Dana; Zayed, Ayman; Momani, Munther; Alalawi, Sundus (Jordan Journal of Pharmaceutical Sciences, 2019)
Abstract Background and aims: Oxytocin (OXT), hepatocyte growth factor (HGF) and fibroblast growth factor-21 (FGF-21) were shown to play key roles in different aspects of metabolic syndrome (MetS) and type 2 diabetes mellitus (T2DM). Nevertheless, how OXT correlates – if at all - with the plasma levels of both FGF-21, and HGF is still to be investigated in MetS-pre/T2DM patients. Methods: In a cross-sectional study, 85 MetS-normoglycemic (control) and 90 MetS-preT2DM patients (BMI-, gender- and age-matched) were enrolled. Plasma OXT levels were measured using competitive binding enzyme-linked immunosorbent assay (ELISA), while FGF-21 and HGF levels were measured using sandwich ELISA. The correlations between these biomarkers and between biomarkers and patients’ clinical parameters such as HbA1c, FPG, blood pressure, lipid profile, and body mass index were evaluated. Results: Mean circulating levels of both HGF and FGF-21 were substantially higher in the MetS-pre/T2DM group than in the MetS-control group; HGF (pg/mL) means±SD were 98.06±59.78 vs. 58.8±25.51, p<0.05, and for FGF-21 (ng/mL) 0.41±0.33 vs. 0.28±0.25, p<0.05. Conversely, mean OXT plasma levels (pg/mL) were lower in the MetS-pre/T2DM group than in the MetS-control group (1231.26±555.91 vs. 2201.54±867.50, p<0.05). In the total pool of MetS-participants, plasma OXT levels correlated inversely with both HGF and FGF-21 plasma levels; (Spearman correlation coefficient r = -0.403, p<0.05, N=162) for HGF, and (r = -0.222, p<0.05, N=159) for FGF-21, also HGF plasma levels correlated directly with those of FGF-21 (r = 0.203, p<0.05, N=152). In the total MetS-sample, HGF plasma levels correlated positively whereas OXT levels correlated inversely with HbA1c and FPG (p<0.05; N=175 the whole MetS swtudy population). Conclusions: Unlike the decreased OXT levels HGF and FGF-21 were increased in MetS-pre/T2DM. A direct correlation was found between HGF and FGF-21, and an inverse correlation was observed between OXT and these two biomarkers separately. Furthermore, HGF and OXT levels correlated with the degree of glycemic control. Our findings may have potential to be utilized in the therapeutics of MetS-pre/T2DM.